Curing behavior of epoxidized soybean oil with biobased dicarboxylic acids. (February 2017) - Zeng, Run-Tao; Wu, Ying; Li, Yi-Dong; Wang, Ming; Zeng, Jian-Bing
Abstract: In this study, we report the curing of ESO with biobased dicarboxylic acids (DCAs) with different carbon chain-lengths to synthesize fully sustainable polymers. Both non-isothermal and isothermal curing processes analysis indicated that the curing rate and activation energy decreased with increasing chain-length of DCAs. The optimum COOH/epoxy molar ratio is 0.7 for preparation of ESO/DCA cured product with maximum degree of crosslinking. Addition of 4-N, N -dimethylaminopyridine (DMAP) as a catalyst can efficiently accelerate the curing rate and reduce activation energy. We systemtically studied the effect of chain-length of DCAs on the physical properties of cured products, and found that with increase in chain-length of DCAs, the glass transition temperature of the cured ESO/DCA decreased, the tensile strength and Young's modulus increased while elongation at break decreased, due to the decreased crosslinking density resulted from the increased chain-length between crosslinking sites. All cured ESO/DCA showed excellent thermal stability with initial decomposition temperature of higher than 340 °C.